Long-lasting neutralizing antibodies and T cell response after the third dose of mRNA anti-SARS-CoV-2 vaccine in multiple sclerosis - Maglione, Alessandro; Francese, Rachele; Arduino, Irene; Rosso, Rachele; Matta, Manuela; Rolla, Simona; Lembo, David; Clerico, Marinella (Frontiers in Immunology, 2023)
Background and objectives Long lasting immune response to anti-SARS-CoV-2 vaccination in people with Multiple Sclerosis (pwMS) is still largely unexplored. Our study aimed at evaluating the persistence of the elicited amount of neutralizing antibodies (Ab), their activity and T cell response after three doses of anti-SARS-CoV-2 vaccine in pwMS. Methods We performed a prospective observational study in pwMS undergoing SARS-CoV-2 mRNA vaccinations. Anti-Region Binding Domain (anti-RBD) of the spike (S) protein immunoglobulin G (IgG) titers were measured by ELISA. The neutralization efficacy of collected sera was measured by SARS-CoV-2 pseudovirion-based neutralization assay. The frequency of Spike-specific IFNγ-producing CD4+ and CD8+ T cells was measured by stimulating Peripheral Blood Mononuclear Cells (PBMCs) with a pool of peptides covering the complete protein coding sequence of the SARS-CoV-2 S. Results Blood samples from 70 pwMS (11 untreated pwMS, 11 under dimethyl fumarate, 9 under interferon-γ, 6 under alemtuzumab, 8 under cladribine, 12 under fingolimod and 13 under ocrelizumab) and 24 healthy donors were collected before and up to six months after three vaccine doses. Overall, anti-SARS-CoV-2 mRNA vaccine elicited comparable levels of anti-RBD IgGs, neutralizing activity and anti-S T cell response both in untreated, treated pwMS and HD that last six months after vaccination. An exception was represented by ocrelizumab-treated pwMS that showed reduced levels of IgGs (p<0.0001) and a neutralizing activity under the limit of detection (p<0.001) compared to untreated pwMS. Considering the occurrence of a SARS-CoV-2 infection after vaccination, the Ab neutralizing efficacy (p=0.04), as well as CD4+ (p=0.016) and CD8+ (p=0.04) S-specific T cells, increased in treated COVID+ pwMS compared to uninfected treated pwMS at 6 months after vaccination. Discussion Our follow-up provides a detailed evaluation of Ab, especially in terms of neutralizing activity, and T cell responses after anti-SARS-CoV-2 vaccination in MS context, over time, considering a wide number of therapies, and eventually breakthrough infection. Altogether, our observations highlight the vaccine response data to current protocols in pwMS and underline the necessity to carefully follow-up anti-CD20- treated patients for higher risk of breakthrough infections. Our study may provide useful information to refine future vaccination strategies in pwMS.